Microbe Profile: Euglena gracilis: photogenic, flexible and hardy - Zoltner, Martin; Field, Mark C (Microbiology (Reading, England), 2022)
Euglena gracilis is a unicellular photosynthetic eukaryotic flagellate of the Discoba supergroup, which also encompasses Kinetoplastida and Diplonema. Plastids have green algal origin and are secondarily acquired. The nuclear genome is extremely large and many genes suggest multiple endosymbiotic/gene transfer events, i.e. derivation from prokaryotes of various lineages. E. gracilis is remarkably robust and can proliferate in environments contaminated with heavy metals and acids. Extraordinary metabolic plasticity and a mixotrophic lifestyle confers an ability to thrive in a broad range of environments, as well as facilitating production of many novel metabolites, making Euglena of considerable biotechnological importance.
Keywords: Photosynthesis; Symbiosis; Euglena gracilis; protists; Plastids; secondary endosymbiosis; plastidy; Chlorophyta; fotosyntéza; symbióza; evolution; Euglena; genome